Union Democracy and Union Renewal: The CAW Public Review Board - Eaton, Jonathan (Relations industrielles / Industrial Relations, 2006)
Unions in the current environment are facing renewed pressures to demonstrate internal democracy and accountability. In this context, the Public Review Board (PRB) of the Canadian Auto Workers (CAW) deserves attention. The PRB is a unique institution within the Canadian labour movement: a body outside the union which has the power to make final and binding decisions on issues raised by union members. This paper considers the contribution of the PRB as a support for democratic renewal. The evolution of the PRB, from its origin in 1950s America to its current Canadian embodiment, is described. The decisions of the PRB over its two-decade history in Canada are analyzed and assessed. While recognizing the lasting influence of the narrow, procedural vision charted by the PRB early in its history, the author concludes that the CAW’s PRB is an innovation that merits wider recognition.